2021
DOI: 10.1016/j.fertnstert.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Why are some patients with 45,X Turner syndrome fertile? A young girl with classical 45,X Turner syndrome and a cryptic mosaicism in the ovary

Abstract: A 14-year-old girl with TS showing an exclusively 45,X cell line in lymphocytes, buccal cells, and urine cells in the presence of ovarian follicles. Intervention(s): Laparoscopic unilateral oophorectomy was performed to obtain ovarian cortex tissue for fertility preservation purposes. One cortex fragment was used to determine the number of follicles by serial sectioning and staining, to perform fluorescence in situ hybridization (FISH) analysis and an in vitro growth (IVG) assay. Main Outcome Measure(s): FISH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The authors argued that karyotyping of extraovarian cells was not predictive of the karyotype of ovarian cells in the same patient. This case report also contributes to the explanation of the high number of follicles in our patients [19]. Furthermore, the determination of the rate of normal karyotype cells as approximately 80% in cases with TS who conceived is a data supporting our suggestion.…”
Section: Discussionsupporting
confidence: 84%
“…The authors argued that karyotyping of extraovarian cells was not predictive of the karyotype of ovarian cells in the same patient. This case report also contributes to the explanation of the high number of follicles in our patients [19]. Furthermore, the determination of the rate of normal karyotype cells as approximately 80% in cases with TS who conceived is a data supporting our suggestion.…”
Section: Discussionsupporting
confidence: 84%
“…The research ethics committee and a board of patients and patient representatives approved the TurnerFertility study on the condition that all girls with TS are offered OTC, including those with a monosomic karyotype. Despite the small chances of success in this patient group, literature about nding oocytes in girls with a monosomic karyotype has been published (9,15,33,34). In some cases, healthcare providers had di culty with the idea of performing an invasive procedure when the odds of success in restoring fertility were small.…”
Section: Discussionmentioning
confidence: 98%
“…In women with TS who have structural aberrations involving the X chromosome and in mosaic cases, ovarian reserve may persist for a variable period post menarche [23]. However, there is no reliable genotype-phenotype correlation [24,25]; no study has thus far reported a link between the level of TS mosaicism and biomarkers of ovarian reserve (AMH and AFC), and accelerated follicle depletion is still likely to occur in women with TS mosaicism. Fertility preservation in young individuals with TS is considered controversial for several reasons.…”
Section: Discussionmentioning
confidence: 99%